2010
DOI: 10.5539/jas.v2n1p138
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza and Employment Decisions of Poultry Farmers in the Federal Capital Territory of Nigeria

Abstract: The outbreak of Avian Influenza in Nigeria has led to job losses, health problems, reduction in expected income of poultry farmers and a decrease in the demand for poultry products. This study was designed to determine the monetary value of stock lost, identify the determinants of the future employment decisions and the constraints faced by poultry farmers in the Federal Capital Territory of Nigeria. Data for the study was collected from 40 poultry farmers who have suffered losses due to the outbreak of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…In previous studies, outbreaks of AI in commercial farms in Nigeria were reported with high mortality (You & Diao, 2007) as well as the spread to other parts of the country (Monne et al, 2008). Furthermore, the economic loss in money terms is similar to the survey results following the outbreak of AI in Abuja in 2006 where estimated farmers lost millions of naira (Ibrahim et al, 2010) as well as reports of great reduction in the income of both smallholders and commercial poultry farmers following outbreak of AI (Muteia et al, 2011).The highest economic loss due to IBD outbreak was reported in the 2 sampled farms in Gwagwalada which was about ₦5 million. Although, there was no means to evaluate the level of biosecurity retrospectively, the current poor state of biosecurity and absence of a well-defined vaccination schedule in the 2 studied farms in Gwagwalada and 1 in Kuje (small scale) based on the questionnaire survey could be contributory.…”
Section: Discussionsupporting
confidence: 69%
“…In previous studies, outbreaks of AI in commercial farms in Nigeria were reported with high mortality (You & Diao, 2007) as well as the spread to other parts of the country (Monne et al, 2008). Furthermore, the economic loss in money terms is similar to the survey results following the outbreak of AI in Abuja in 2006 where estimated farmers lost millions of naira (Ibrahim et al, 2010) as well as reports of great reduction in the income of both smallholders and commercial poultry farmers following outbreak of AI (Muteia et al, 2011).The highest economic loss due to IBD outbreak was reported in the 2 sampled farms in Gwagwalada which was about ₦5 million. Although, there was no means to evaluate the level of biosecurity retrospectively, the current poor state of biosecurity and absence of a well-defined vaccination schedule in the 2 studied farms in Gwagwalada and 1 in Kuje (small scale) based on the questionnaire survey could be contributory.…”
Section: Discussionsupporting
confidence: 69%
“…The outbreak of HPAI virus in Nigeria was first reported in February 2006 at a commercial farm in the northwestern zone (PACE, 2006; Ugwu, 2007; Ibrahim et al., 2010). Since then, it has spread to over half of the states in the country, mainly in commercial poultry farms with no reports in the free‐range flocks.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from confirmed outbreaks in Africa shows how avian flu has direct implications for the poultry sector and for households that draw incomes from poultry rearing and trade (Birol et al ., 2010a; Okello et al ., 2010). However, the importance of livestock in Africa means that avian flu could also have indirect or economy‐wide effects on other sectors and households (Ayele et al ., 2010; Diao, 2009; Ibrahim et al ., 2010). This complicates the design of appropriate government responses, especially when outbreaks have yet to occur (Fischhoff et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%